A role for the cytoplasmic DEAD box helicase Dbp21E2 in rhodopsin maturation and photoreceptor viability. - Hibbard, K.L.; O'Tousa, J.E. (Journal of Neurogenetics, 2012)
The Dbp21E2 (DEAD box protein 21E2) is a member of a family of DEAD box helicases active in RNA processing and stability. The authors used genetic mosaics to identify mutants in Dbp21E2 that affect rhodopsin biogenesis and the maintenance of photoreceptor structure. Analysis of a green fluorescent protein (GFP)-tagged Rh1 rhodopsin construct placed under control of a heat shock promoter showed that Dbp21E21 fails to efficiently transport Rh1 from the photoreceptor cell body to the rhabdomere. Retinal degeneration is not dependent on the Rh1 transport defects. The authors also showed that GFP- and red fluorescent protein (RFP)-tagged Dbp21E2 proteins are localized to discrete cytoplasmic structures that are not associated with organelles known to be active in rhodopsin transport. The molecular genetic analysis described here reveals an unexpected role for the Dbp21E2 helicase and provides an experimental system to further characterize its function.